Prenatal exposure to metal mixtures and newborn neurobehavior in the Rhode Island Child Health Study. Issue 1 (28th February 2022) - Tung, Pei Wen; Burt, Amber; Karagas, Margaret; Jackson, Brian P.; Punshon, Tracy; Lester, Barry; Marsit, Carmen J.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Prenatal exposure to metals can affect the developing fetus and negatively impact neurobehavior. The associations between individual metals and neurodevelopment have been examined, but little work has explored the potentially detrimental neurodevelopmental outcomes associated with the combined impact of coexisting metals. The objective of this study is to evaluate prenatal metal exposure mixtures in the placenta to elucidate the link between their combined effects on newborn neurobehavior. Method: This study included 192 infants with available placental metal and NICU Network Neurobehavioral Scale data at 24 hours–72 hours age. Eight essential and nonessential metals (cadmium, cobalt, copper, iron, manganese, molybdenum, selenium, zinc) detected in more than 80% of samples were tested for associations with atypical neurobehavior indicated by NICU Network Neurobehavioral Scale using logistic regression and in a quantile g-computation analysis to evaluate the joint association between placental metal mixture and neurobehavioral profiles. Results: Individually, a doubling of placental cadmium concentrations was associated with an increased likelihood of being in the atypical neurobehavioral profile (OR = 2.39; 95% CI = 1.05 to 5.71). In the mixture analysis, joint effects of a quartile increase in exposure to all metals was associated with 3-fold increased odds of newborns being assigned to the atypical profile (OR = 3.23; 95% CI = 0.92 to 11.36), with cadmium having the largest weight in the mixture effect. Conclusions: Prenatal exposure to relatively low levels of a mixture of placental metals was associated with adverse newborn neurobehavior. Examining prenatal metal exposures as a mixture is important for understanding the harmful effects of concomitant exposures in the vulnerable populations.